Narrative Structure Analysis of MTs Students from a Gender Perspective - Mahriyuni; Erikson Saragih; Dedi Rahmad Sitinjak; Nurlela; Deliana (English Lecturers and Teachers Association (ELTA), 2025)
This study aims to describe the narrative structure of fables written by students of MTs YP H. Datuk Abdullah, to compare male and female students’ narratives, and to analyze the influence of gender perspectives on story construction. The analysis framework employs Todorov’s (1971) narrative structure theory, consisting of five stages: equilibrium, disruption, recognition, repair, and new equilibrium. A descriptive qualitative method was used with 32 seventh-grade students (15 male and 17 female) selected purposively as the subjects. Data were collected through fable writing tasks and semi-structured interviews, and validated through methodological triangulation, peer debriefing, and member checking. The results show significant differences: the majority of male students (11 out of 15, 73%) produced concise, action-oriented narratives that went straight to the core of the story with a simplified Todorov structure, while 4 students (27%) wrote longer or slightly more reflective narratives. In contrast, the majority of female students (12 out of 17, 71%) produced longer, expressive, and reflective narratives, emphasizing social relationships, emotions, and moral values with a complete Todorov structure, while 5 students (29%) produced shorter or less reflective narratives. The synthesis indicates that male students tend to emphasize physical action and outcomes, whereas female students emphasize emotional reflection, social interaction, and moral messages. These findings have implications for developing gender-responsive narrative writing strategies, enabling teachers to adapt methods that optimize students’ cognitive and expressive abilities. Keywords : Fable; Gender; Todorov’s Narrative Structure